Implementation of Lesson Study-Based Problem Based Learning Learning Model to Improve Creative Thinking Ability (KBK) - Sari, Adhelia Rahma; Winaryati, Eny; Hidayah, Fitria Fatichatul (Proceeding International Conference on Lesson Study, 2023)
This study aims to describe the implementation of the Problem Based Learning learning model to improve students’ Creative Thinking Ability (KBK) in acid-base chemistry subject. This type of research is descriptive quantitative through Lesson Study activities which consist of three stages, namely Plan, Do, See with the PBL model. The subjects used were class XI students of SMA Negeri 1 Lasem. The data collection method is by giving LKPD questions, observations, field notes, and documentation. The observer’s observation results are supported by documentation data in the form of photos and videos. The results of this study indicate that the classification of students’ Creative Thinking Ability (KBK) in the first cycle and the second cycle is classified as fulfilling the indicators of the Creative Thinking Ability (KBK) dimension. Therefore, the Dimensions of Students’ Creative Thinking Ability (KBK) in chemistry subjects can be improved by using Lesson Study-based Problem Based Learning.